Pricing Asian power options under jump-fraction process - Peng, Bin (2012)
A framework for pricing Asian power options is developed when the underlying asset follows a jumpfraction process. The partial differential equation (PDE) in the fractional environment with jump is constructed for such option using general Itô’s lemma and self-financing dynamic strategy. With the boundary condition, an analytic formula for the option with geometric average starting at any time before maturity is derived by solving the PDE, and the option with arithmetic average is evaluated in Monte Carlo simulation using control variate technique with the help of the above analytic solution. Overwhelming numerical evidence indicates that the technique proposed is computationally efficient and dramatically improves the accuracy of the simulated price. Moreover, this study will pave a novel way to copy with the option contracts based on thinly-traded assets like oil, or currencies or interest rates. DOI: https://doi.org/10.1016/S2077-1886(12)70002-1